DIGITAL-BASED LEARNING STRATEGIES AND INNOVATIONS IN ISLAMIC RELIGIOUS EDUCATION - Turky; Muhammad Nur Cholil; Fairuz Zacky Taufiq Hidayat; Ro’ifah (Al-Wihdah: Jurnal Pendidikan Islam, 2025)
The advancement of digital technology has brought significant changes in education, including Islamic Religious Education (PAI), requiring teachers to adapt learning methods to remain relevant for the digital generation. This study employed a library research approach, analyzing accredited national journals, proceedings, and scientific books related to strategies and innovations in digital-based PAI. The study aims to identify effective strategies and innovations to enhance students’ understanding, motivation, and internalization of moral and spiritual values. Findings reveal that effective digital-based PAI strategies include strengthening Qur’an and Hadith literacy, Islamic digital literacy, values and ethics reinforcement, teacher facilitation, affective enhancement through interactive experiences, and moderation with community building. Learning innovations such as interactive multimedia, digital-based creative projects, Islamic digital literacy, and gamified assessments were found to improve conceptual understanding, 21st-century skills, learning motivation, critical thinking, and creativity. Teachers act as facilitators, guiding students to use technology ethically, including principles of tabayyun and digital etiquette. The integration of digital and face-to-face learning (blended learning) enables a balance between content mastery and character development. This study emphasizes the importance of digital-based PAI learning innovations as a creative, relevant, and sustainable model aligned with Islamic educational objectives, while supporting the development of Islamic digital literacy, motivation, and moral and spiritual character formation for the digital generation.